Pendampingan Penerapan Rekam Medis Elektronik dan Mendukung Alih Media Rekam Medis di Puskesmas Salimbatu - Supian; Iswaliyah, Rabialda; Sakinah; Fadila, Tiwi; Elicukia; Sari, Irda; Syahidin, Yuda; Yunengsih, Yuyun; Gunawan, Erix; Ulfah, Annisa (LPPM Politeknik Piksi Ganesha, 2024)
Devotion focuses on the efforts of socialization and assistance conducted to implement Electronic Health Records (EHR) at Salimbatu Public Health Center. EHR represents a technological breakthrough in medical data management aimed at enhancing efficiency, accuracy, and quality healthcare services. However, for a successful adoption of EHR in primary care clinics, it is crucial to understand and address both social and technical challenges that may arise. This study employs a case study approach, collecting data through interviews with clinic staff, observations, and document analysis related to EHR implementation Devotion findings indicate that the socialization of EHR at Salimbatu Public Health Center involves intensive training for clinic staff, regular meetings to discuss progress, and patient education regarding the benefits of EHR. Technical support is provided through a team of experts who offer technical assistance, system improvements, and day-to-day issue resolution. The outcomes of this implementation include a significant enhancement in medical data management efficiency, reduced human errors, and improved patient services. Socialization and assistance are vital components for the successful implementation of EHR at Salimbatu Public Health Center